(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the physical, mechanical, and wood machining properties of 10 clonal progenies with 12 years of age aiming to produce furniture. A total of 10 progenies and three trees per progenies were used, totalling 30 trees analyzed. The basic density ranged from 0.404 g.cm-3 (IAC 301) to 0.495 g.cm-3 (IAC 326), being it considered a light wood. The anisotropy coefficient values ranged from 1.05 (IAC 40) to 1.68 (PB 330) considered low to medium dimensional instability allowing the use of wood to produce furniture with low dimensional movements. In the compression test most clones fall under class C30. For MOR and MOE, it was observed greater values for IAC 326 (11666 MPa) and GT1 (9575 MPa). In wood machining tests, slightly raised large and few defects on the surface, being them considered easy to work. The results obtained for Hevea brasiliensis, 12 years old, allow us to affirm that wood from a younger age is an alternative for furniture production and will consequently contribute to the reduction of the exploitation and degradation of native forests in Brazil for this purpose.